INFLUENCE OF THE PROFESSIONAL LOAD ON CARDIOVASCULAR SYSTEM INDICATORS AT DENTISTS - Melnikova, S.V.; Zaporozhets, T.N. (World of Medicine and Biology, 2012)
The state of the cardiovascular system was performed in healthy dentists aged 35 to 45 years professional experience subjects from 12 to 20 years. Revealed the presence of a causal relationship between stress at work and changes in the cardiovascular system. By the criterion of orientation changes in the indices of the cardiovascular system in dentists found hypersthenic and hyposthenic types of response.
Keywords: cardiovascular system; dentists’ professional activity; outpatient dental reception